Pengaruh Promosi Melalui Media Sosial Terhadap Pemanfaatan Perpustakaan Umum Kota Solok - Yolan Melani Putri; Cut Afrina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The main problem in this study is that the library maximizes promotion through social media because librarians rarely do promotions through Instagram posts, Facebook, and library websites, the lack of use of the Solok City Public Library by visitors, due to the covid'19 pandemic, and the lack of creativity of librarians in using social media as a means of promotion of the use of the library. The type of research used is causal associative with a quantitative approach. This research was conducted at the Public Library of Solok City by using a questionnaire as a research instrument. Questionnaires were distributed to 81 respondents using a simple random sampling technique. Data were analyzed using descriptive statistical methods by describing quantitative data. The results obtained regarding the effect of promotion through social media on the use of the Solok city public library showed that the variable of promotion through social media was 3.21 and the variable of library utilization was 3.13. So it can be concluded that the effect of promotion through social media on the utilization of the Solok city public library is good. In the grand mean test, the collection utilization indicator is said to be good with a grand mean value of 3.06. In the grand mean test, the indicator of the utilization of the search facility is said to be good with a grand mean value of 3.18. In the grand mean test, the use of library services is said to be good with the grand mean value of 3.15. Promotion through social media affects library utilization by 54%, while the remaining 46% is explained by other factors not examined. The effect of variable X on variable Y has a significant effect of 0.037 at the probability level < 0.05. Thus it can be concluded that there is a significant influence between promotion through social media on library utilization